2008
DOI: 10.1038/oby.2008.435
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes of Gut Microflora and Enzyme Activity in Rat Pups Exposed to Fat‐rich Diet

Abstract: The aim of this study was to investigate the effect of a high‐fat (HF)/energy diet on the intestinal microbiota, the alkaline phosphatase (AP) activity, and related parameters of growth and obesity during the suckling and weaning periods in male Sprague‐Dawley rats. From birth, nutrition in suckling pups was manipulated by feeding rat dams either HF or a standard diet, and then after weaning, by exposure of experimental pups to the HF, and control rats to normal diet. On days 15, 20, 40 the numbers of 2 microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 49 publications
2
51
1
Order By: Relevance
“…Besides, no relationship was found between plasma lipids and higher BW gain in lean rats. Previous studies have reported that the high ratio of Firmicutes to Bacteriodetes may assist the obese host harvest more energy from the diet (24)(25)(26) . However, this opinion has not been confirmed by recent studies; in fact, the opposite results have been reported (10,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, no relationship was found between plasma lipids and higher BW gain in lean rats. Previous studies have reported that the high ratio of Firmicutes to Bacteriodetes may assist the obese host harvest more energy from the diet (24)(25)(26) . However, this opinion has not been confirmed by recent studies; in fact, the opposite results have been reported (10,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity as a multifactorial disease results from interaction of genetic and environmental factors. Recent studies have demonstrated that obesity in rats is also closely related to disturbance of two dominant divisions of gut bacteria, especially increase in the Firmicutes and reduction of the Bacteroidetes (11,20). Supplementation with apple-derived pectin in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regarding the role of intestinal enzymes, AP is considered as a brush border-bound representative enzyme that has a broad range of roles, involving regulation of lipid absorption (16). Its activity increased markedly after fat feeding (13,17,20) and decreased after fasting, while refeeding elevated it to the pre-fasting level (26). AP in rodents is present at its highest level in the duodenum, and its activity decreases gradually toward the jejunum and ileum (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that the intestinal microbiota involves in metabolome of the host, thus promotes actively fat accumulation and weight gain and sustains indirectly a lowgrade systemic inflammation especially when imbalanced, and consequently, enhances the risk for complex, multifactorial diseases such as insulin resistance, diabetes, obesity and cardiovascular diseases. The search of global obesity epidemic led to the growing evidences about the possible roles of intestinal microbiota in these respects [180,181,182]. Claus et al [170] has noted that the colonization of the gut microbiota was associated with a rapid increase in body weights of animals up to 4% within 5 days of colonization.…”
Section: Intestinal Microbiotamentioning
confidence: 99%